Pengaruh Teknik Relaksasi Nafas Dalam dan Masase Terhadap Penurunan Skala Nyeri Pasien Pasca Apendiktomi di Ruang Bedah RSUD Dr. M. Zein Painan: The Effect of Deep Breathing Relaxation Techniques and Massage on the Reduction of Pain Scale in Post-Appendectomy Patients in the Surgical Room at Dr. M. Zein Painan Regional Hospital - Yusrizal; Zarni Zamzahar; Eliza Anas (NERS Jurnal Keperawatan, 2012)
The purpose of this study was to determine the effect of deep breathing relaxation techniques and massage on reducing pain in post-appendectomy patients in the Surgical Room at Dr. M. Zein Painan Hospital. This research uses a quasi-experimental design with a pretest-posttest design with a control group. The sampling technique is purposive sampling with a sample of 20 people. Data collection is done by using a verbal description scale (verbal descriptor scale) for the pain scale. Data analysis is done with a paired t-test to assess the differences before and after the intervention in each group and the Mann-Whitney test to assess differences between groups. The results of this study indicate that the average pain level difference in the control group pretest-posttest is 2.30, and the average difference in the pain level in the experimental group before and after deep breathing relaxation techniques and massage is 3.50. Results of statistical tests for the control and experimental groups show a p-value of 0.000 (p < 0.05). It is concluded that the technique of deep breathing and relaxation massage can reduce the pain scale in post-appendectomy clients. It is advisable to apply deep breathing relaxation techniques and massage as one of the non-pharmacological techniques to reduce pain in post-appendectomy clients.